Electrochemical sensing of nicotine using laser-induced graphene screen-printed electrode - Badrol Hisham, Balqis Nurnadia; Ab Rahim, Rosminazuin; Nordin, Anis Nurashikin; Md Ralib @ Md Raghib, Aliza 'Aini; Za'bah, Nor Farahidah; Tung, Lun Hao; Mohd Zain, Zainiharyati (IIUM Press, 2025)
Nicotine is one of the major addictive substances in tobacco plants, which caused a global pandemic. Rapid detection of nicotine is crucial to allow quick identification of harmful substances that will cause significant health risks, especially with the recent rise in electronic cigarettes. Since smoking cessation programs are typically limited to screening, awareness, consultation, medication, and follow-up activities, there is a need for a device to check the nicotine level in former smokers at the end of the programs. However, most of the current nicotine detection is based on chromatography technology, which involves complicated sample pre-treatment and bulky and expensive instruments. Thus, screen-printing technology employing electrochemical detection is a promising solution as it offers a simple and portable setup for nicotine detection. Yet, conventional screen-printed electrodes (SPE) have relatively low sensitivity and need modification to improve the electrode material. Therefore, this work aims to investigate the performance of laser-induced graphene (LIG) as SPE-modified electrodes to detect the presence of nicotine through electrochemical measurements. A finite element simulation was conducted to investigate laser power's effect on the induced graphene's quality. The CO2 laser with 3W laser power, Dots per inch (DPI) of 1200, and a laser speed of 13% was used to fabricate the LIG sensor on a Kapton substrate. Material characterizations such as SEM, EDX, and Raman spectra were performed on the fabricated LIG-SPE to confirm the presence of LIG. Cyclic voltammetry (CV) measurement was done using 0.1M [Fe (CN)6]3-/4- and 0.1M KCL to find the suitable scan rates. At a fixed scan rate of 50 mV/s, the sensor's performance was analyzed using 0.1M of nicotine with 3 different phosphate buffer solutions (PBS) of pH 5, pH 7, and pH 9 at different nicotine concentrations. Nicotine with PBS pH 5 solution was found to be the optimum measured solution, with the value obtained for R² having the highest value of 0.9988 and the lowest LOD of 4.2183 μM. The proposed electrochemical sensing of nicotine using a laser-induced graphene screen printed electrode can detect nicotine with high linearity at different pH levels of PBS buffer solution. ***** Nikotin adalah salah satu bahan ketagihan utama dalam tumbuhan tembakau yang menyebabkan pandemik global. Pengesanan cepat nikotin adalah penting bagi membolehkan pengecaman cepat bahan merbahaya yang menyebabkan risiko kesihatan ketara terutamanya dengan peningkatan rokok elektronik pada masa sekarang. Memandangkan program berhenti merokok biasanya terhad kepada pemeriksaan, kesedaran, perundingan, ubat-ubatan dan aktiviti susulan, terdapat keperluan bagi peranti memeriksa tahap nikotin dalam bekas perokok pada akhir program. Walau bagaimanapun, kebanyakan pengesanan nikotin semasa adalah berdasarkan teknologi kromatografi, di mana melibatkan sampel pra-rawatan rumit, instrumen besar dan mahal. Oleh itu, teknologi percetakan skrin yang menggunakan pengesanan eletrokimia adalah penyelesaian bermakna kerana ia menawarkan persediaan mudah dan mudah alih bagi mengesan nikotin. Namun, skrin-cetakan elektrod konvensional (SPE) mempunyai sensitiviti rendah dan memerlukan pengubahsuaian bagi menambah baik bahan elektrod. Oleh itu, kajian ini adalah untuk menyiasat prestasi laser graphen teraruh (LIG) sebagai elektrod SPE yang diubah suai bagi mengesan kehadiran nikotin melalui pengukuran elektrokimia. Simulasi unsur terhingga telah dijalankan bagi melihat kesan kuasa laser ke atas kualiti graphen teraruh. Laser CO? dengan kuasa laser 3W, dot per inci (DPI) sebanyak 1200, dan kelajuan laser sehingga 13% telah digunakan bagi mengfabrikasi pengimbas LIG pada substrat Kapton. Pencirian bahan sperti SEM, EDX, dan spektrum Raman dilakukan pada LIG-SPE yang direka bagi mengesahkan kehadiran LIG. Pengukuran voltametri kitaran (CV) dilakukan menggunakan 0.1M [Fe (CN)6]3-/4- dan 0.1M KCL bagi mencari kadar imbasan yang sesuai. Pada kadar imbasan tetap 50 mV/s, prestasi pengimbas dianalisa menggunakan 0.1M nikotin dengan 3 larutan penimbal fosfat (PBS) berbeza pH 5, pH 7, dan pH 9 pada kepekatan nikotin berbeza. Nikotin dengan larutan PBS pH 5 didapati sebagai larutan optimum, dengan nilai R² tertinggi 0.9988 dan LOD terendah 4.2183 ?M. Kesimpulannya, pengimbas elektrokimia nikotin menggunakan laser elektrod skrin bercetak graphen teraruh dapat mengesan nikotin dengan pemalaran tinggi pada pH larutan penimbal PBS yang berbeza.